Toward a Hermeneutical Theory of International Human Rights Education. Issue 4 (20th August 2013) - Al‐Daraweesh, Fuad; Snauwaert, Dale T.
Abstract The purpose of this essay is to articulate and defend the epistemological foundations of international human rights education from the perspective of a hermeneutical interpretive methodology. Fuad Al‐Daraweesh and Dale Snauwaert argue here that this methodology potentially alleviates the challenges that face the cross‐cultural implementation of human rights education. While acknowledging the necessity of global human rights awareness, the authors maintain that local cultural conceptualization is imperative to the negotiated, local embrace of human rights. A critical, interpretive pedagogy emerges from grounding human rights education in a hermeneutic methodology. Thus, Al‐Daraweesh and Snauwaert advocate taking a hermeneutical approach in order to enlarge the scope and meaning of international human rights education.